2017
DOI: 10.1371/journal.pone.0180381
|View full text |Cite
|
Sign up to set email alerts
|

RpoS role in virulence and fitness in enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) is a diarrheagenic pathogen that afflicts infants in developing countries. The most important virulence trait of EPEC is its ability to intimately adhere to cells in the small intestine, and to elicit diarrhea. The alternative sigma factor RpoS is involved in the virulence of several bacterial species. RpoS coordinates the general stress response and accumulates in cells under stress or in the stationary phase. RpoS levels differ across E. coli strains. High-RpoS strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…However, limited information is available regarding the role of RpoS in Shewanella sp. For the stress challenge, S. baltica X7 positively regulated the stress resistance in heat, ethanol and H 2 O 2, as previously reported in other bacterial species such as Y. pseudotuberculosis, E. coli and P. fluorescens (Guan et al 2015;Mata et al 2017;Liu et al 2018). The survival rate was significantly decreased in MrpoS mutant compared to wild type strain of S. baltica after exposure to these stress conditions.…”
Section: Regulation Of Stress Resistance By Rpossupporting
confidence: 72%
See 1 more Smart Citation
“…However, limited information is available regarding the role of RpoS in Shewanella sp. For the stress challenge, S. baltica X7 positively regulated the stress resistance in heat, ethanol and H 2 O 2, as previously reported in other bacterial species such as Y. pseudotuberculosis, E. coli and P. fluorescens (Guan et al 2015;Mata et al 2017;Liu et al 2018). The survival rate was significantly decreased in MrpoS mutant compared to wild type strain of S. baltica after exposure to these stress conditions.…”
Section: Regulation Of Stress Resistance By Rpossupporting
confidence: 72%
“…Some reports have shown that rpoS is also associated with the expression of virulence factor and spoilage potential. For instance, RpoS in E. coli LRT9 positively regulated adherence to epithelial cells (Mata et al 2017). RpoS in Y. pseudotuberculosis regulated the expression of T6SS, flagellum and also biofilm formation through coordinating the synthesis of exopolysaccharides (Guan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other types of E. coli may also show specific niche adaptation involving RpoS. For example, enteropathogenic E. coli (EPEC) (which can cause infant diarrhea), RpoS is, as expected, required for stress resistance but has a differential effect on adherence to epithelial cells that is strain-dependent (Mata et al, 2017).…”
Section: Variability Of Rpos In Other Strains Of E Colimentioning
confidence: 85%
“…While many bacterial gene regulation studies have employed exponential phase cultures, examining bacterial adaptation to stationary phase in laboratory culture may be a useful proxy for understanding how bacteria transition to suboptimal growth conditions in the natural environment. During stationary phase adaptation, the E. coli cell undergoes morphological remodeling (Lange and Hengge-Aronis, 1991), becomes resistant to specific stresses (e.g., heat and oxidative stress; Vidovic et al, 2012;Mata et al, 2017), and substantially reduces overall macromolecule biosynthesis (Yoshida et al, 2018). Translation is down-regulated by the dimerization of ribosomes from the active 70S form to a quiescent 100S form (Yoshida et al, 2019).…”
Section: Rpos Evolutionmentioning
confidence: 99%
“…Despite its central role in general stress response, rpoS variants with attenuated activity have been observed frequently during prolonged phases of slow growth (8,10,22 ). Strains with attenuated rpoS display an improved ability to utilize poor carbon sources such as succinate and acetate but with a suboptimal stress response, whereas the opposite is true for strains with abundant RpoS (6,8,11,21,(23)(24)(25). Thus, polymorphism at rpoS represent trade off between selfpreservation and nutritional competence (6,8,26).…”
Section: Introductionmentioning
confidence: 99%